1998
DOI: 10.1002/elps.1150190109
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous chiral separation of 3,4‐methylenedioxymethamphetamine (MDMA), 3‐4‐methylenedioxyamphetamine (MDA), 3,4‐methylenedioxyethylamphetamine (MDE), ephedrine, amphetamine and methamphetamine by capillary electrophoresis in uncoated and coated capillaries with native β‐cyclodextrin as the chiral selector: Preliminary application to the analysis of urine and hair

Abstract: The importance of the chiral analysis of amphetamine-related substances in both clandestine preparations and biological samples is widely recognized. For this purpose, capillary electrophoresis was successfully applied by several authors, but only few reports concerned ring-substituted amphetamines, which represent the main components of "ecstasy", a widely abused "recreational" substance. In the present work, the simultaneous chiral analysis of ephedrine, amphetamine, methamphetamine, 3,4-methylenedioxymetham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 17 publications
4
23
1
2
Order By: Relevance
“…1, who was a CYP2D6 poor metabolizer, had the highest R/S-MDMA ratio in the hair segment corresponding to the time of intake and the nail scraping whereas the ratio in the nail clipping was in the range of the extensive CYP2D6 metabolizers ( Figure 3A). To our knowledge, there are two reports on chiral analysis of MDMA and MDA in hair samples from suspected or self-declared MDMA users [41][42][43]. Enantiomeric ratios for MDMA and MDA from our controlled intake study are in concordance with hair findings reported by Martins et al from a study with self-declared MDMA users after controlled MDMA administration [41].…”
Section: Mdma and Mda In Nail Samples And Comparison To Hairsupporting
confidence: 90%
“…1, who was a CYP2D6 poor metabolizer, had the highest R/S-MDMA ratio in the hair segment corresponding to the time of intake and the nail scraping whereas the ratio in the nail clipping was in the range of the extensive CYP2D6 metabolizers ( Figure 3A). To our knowledge, there are two reports on chiral analysis of MDMA and MDA in hair samples from suspected or self-declared MDMA users [41][42][43]. Enantiomeric ratios for MDMA and MDA from our controlled intake study are in concordance with hair findings reported by Martins et al from a study with self-declared MDMA users after controlled MDMA administration [41].…”
Section: Mdma and Mda In Nail Samples And Comparison To Hairsupporting
confidence: 90%
“…6,7) However, few reports have focused on DMA, even though the analysis of DMA is required in Japanese drug abuse situations.…”
Section: Drug Samplesmentioning
confidence: 99%
“…De nombreuses études sont décrites sur le plasma ou sur l'urine pour les dérivés amphétaminiques et analogues (22,37), la méthaqualone (58) Avec l'utilisation de sélecteurs chiraux dans le tampon de migration, TEC s'est énormément développée. Elle est devenue une technique simple et peu coûteuse pour la séparation et l'analyse des énantiomères.…”
Section: -Sang Et Urineunclassified
“…L'équipe de Thormann est certainement encore la plus active dans l'analyse des milieux biologiques (10-12) et il décrit dans une revue de la littérature sur les années 1997 et 1998 les progrès récents de TEC et les applications en routine en toxicologie clinique et médico-légale. Des études plus spécifiques se développent : TEC est en train de devenir l'approche la plus commune pour l'analyse chirale de nombreux médicaments et substances illicites (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) (28). Cependant, l'injection directe de l'échantillon reste peu appliquée à l'analyse toxicologique de prélè-vements biologiques en raison de la faible concentration des xénobiotiques.…”
Section: -Introductionunclassified